2017
DOI: 10.1186/s13059-017-1282-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-guided gene prioritization reveals new insights into the mechanisms of chemoresistance

Abstract: BackgroundIdentification of genes whose basal mRNA expression predicts the sensitivity of tumor cells to cytotoxic treatments can play an important role in individualized cancer medicine. It enables detailed characterization of the mechanism of action of drugs. Furthermore, screening the expression of these genes in the tumor tissue may suggest the best course of chemotherapy or a combination of drugs to overcome drug resistance.ResultsWe developed a computational method called ProGENI to identify genes most a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…Various studies have suggested that including information on the interaction of the genes (and their protein products) or their involvement in different pathways can improve the accuracy of different bioinformatics tasks [26] such as gene prioritization [27], gene function prediction [28], gene set characterization [29], and tumor subtyping [30]. Since the genes (and their protein products) involved in a drugs mechanism of action biochemically and functionally interact with each other, we sought to determine whether including these interactions could improve CDR prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have suggested that including information on the interaction of the genes (and their protein products) or their involvement in different pathways can improve the accuracy of different bioinformatics tasks [26] such as gene prioritization [27], gene function prediction [28], gene set characterization [29], and tumor subtyping [30]. Since the genes (and their protein products) involved in a drugs mechanism of action biochemically and functionally interact with each other, we sought to determine whether including these interactions could improve CDR prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge-guided gene prioritization: KnowEnG also offers a knowledge-guided mode of this pipeline, where the ProGENI algorithm of Emad et al 27 is used to incorporate a network encoding prior knowledge into the identification of phenotype-related genes (Figure 3A), using random walk-based techniques similar to those used in the NBS clustering approach 18 . We had previously tested ProGENI on the task of prioritizing drug response-related genes.…”
Section: A Supplementary Methods Sm7)mentioning
confidence: 99%
“…Knowledge-guided gene prioritization. KnowEnG also offers a knowledge-guided mode of this pipeline, where the ProGENI algorithm of Emad and colleagues [47] is used to incorporate a network encoding prior knowledge into the identification of phenotype-related genes (Fig 4A), using random walk-based techniques similar to those used in the NBS clustering approach [11]. We had previously tested ProGENI on the task of prioritizing drug responserelated genes.…”
Section: Case Study 2: Gene Prioritization For Tumor Typesmentioning
confidence: 99%
“…is available on a collection of samples, along with a phenotypic score for each sample. For instance, Emad and colleagues [47] used this pipeline to identify genes whose basal expression in a cancer cell line is predictive of the cell line's response to a cytotoxic treatment. Similar analyses have been performed in other published studies [48], although without incorporating a knowledge network.…”
Section: Applications To Other Biological Domainsmentioning
confidence: 99%